Youth insights on factors influencing housing purchase and rental decisions - Mohamed Saraf, Mohamad Haizam; Radzi, Muhammad Eidlan Hakimi; Ramli, Syahmimi Ayuni; Md Wadzir, Mohammad Fitry (UiTM Cawangan Perlis, 2025)
Deciding on purchasing or renting a house are two significant financial decisions as it involves a large proportion of one’s expenses, specifically to the youth. Although the property market price index in Malaysia statistically shows an increase every year as observed by the National Property Information Centre (NAPIC), demand for purchase still remains stagnant in the housing market. With inflation and the ringgit's depreciation, purchasing or renting a house possesses difficulties for youth to consider after they have been employed. Previous published literature on house decision is more focused on young professionals, investors and green homes, leaving a gap in the study of youth, where their perspectives are limited to assess. As it is prevalent to understand their perspectives, this research aims to fill a research gap by identifying the key factors that influence youth whether to purchase or rent in residential properties with. A quantitative approach was employed using a questionnaire for data collection. The results were obtained from mean analysis which indicated facilities and amenities and the country's economic stability attributes as highly influenced the decisions of house purchase or rental with 4.82 and 4.80 mean values respectively. The results contribute to the understanding of youth perspectives on housing and renting issues that might have an effect on the real estate market demand and supply policy and interventions, specifically on the residential real estate market signifying the present state of research.